WHAT ARE THE ADVANTAGES OF AMERICAN EDUCATION SYSTEM? (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In this article, the educational system of America, which is one of the most developed countries in the world, its specific features, types of education and stages are described in sequence. It reveals a number of features of preschool